PENENTUAN BANTUAN MODAL WIRAUSAHA BARU MENGGUNAKAN METODE FUZZY INFERENSI SYSTEM (FIS) MAMDANI - Mahmudi, Ahmad Aviv; Fatkhudin, Aslam (STIE YPPI Rembang, 2013)
Employment growth is slower than the growth of the labor force resulting in unemployment that affect the incidence of poverty. Efforts to improve the local economy is done through the provision of Entrepreneurial Capital Assistance. Entrepreneurial Capital Assistance is intended for people who are creative and innovative people who already have a business but need additional capital for business development. The method can be used to implement such a decision support system using the Fuzzy Inference System with Mamdani method. Fuzzy logic and fuzzy set theory shows great potential to effectively menyelesain uncertainty problems.DSS was developed to assist policy makers in this case Dinsosnakertrans in choosing micro entrepreneurs who applied for assistance with the best possible outcomes for each calculationderived from the criteria desired by policy makers.Keywords : entrepreneurship , Mamdani FIS